Assessment of Pond Water Quality for Fish Culture: A Case Study of Santosh Region in Tangail, Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
This study deals with the assessment of pond water quality for fish culture by measuring various physicochemical parameters of water for fish culture from the seven identified ponds situated at Santosh region of Tangail Sadar Upazila. The parameters including temperature, pH, DO, BOD, transparency, TDS, EC, acidity, alkalinity and hardness were investigated on 7 ponds viz. (1) Peer Sahjaman Dighi, (2) Bagbari Pond, (3) Aat Gazar pond, (4) Ayenamohol Pond, (5) Shahid Janani Jahanara Imam Hall (SJJIH) pond, (6) Raja pond, and (7) Rani pond. The obtained values of the investigated parameters were temperature 29-38.3°C, pH 6.8- 7.12, DO 1.1-6.9 mg/l, BOD 1.4-4.2 mg/l, transparency 32.5-57.5 cm, TDS 85-164 mg/l, EC 138-274 ?s/cm, acidity 20-36.3 mg/l, total alkalinity 43.5-62.5 mg/l and hardness 20-27 mg/l. All the values were compared with the water quality standards for fish culture. The comparative analysis showed that most of the water quality parameters of the 7 ponds were suitable for fish culture while the temperatures recorded were higher in most cases than the desired level, and transparency, TDS and DO level were also fluctuated highly. From this investigation, it is recommended that necessary steps should be undertaken to improve the water quality of the ponds to a suitable level for fish culture. Steps should be implemented in such a way that they not ensure high yield fish production only to bring economic benefit but also conserve environmental qualityDOI: http://dx.doi.org/10.3329/jesnr.v6i2.22112 J. Environ. Sci. & Natural Resources, 6(2): 157-162 2013